Repeat-dose toxicity of human umbilical cord mesenchymal stem cells via subcutaneous injection in NOG mice - Xia, Lijuan; Shao, Jinjin; Yang, Qian; Zhang, Chengda; Xie, Zhiqi; Wang, Linying; Xu, Cong; Zhang, Siming; Liu, Jing; Liu, Fang; Shi, Yuhua; Gu, Liqiang; et al. (Frontiers in Cell and Developmental Biology, 2025)
BackgroundStem cell therapy shows promise for treating skin diseases and enhancing medical aesthetics. However, safety data for subcutaneous injection of stem cells remain limited. In this study, we evaluated the toxicity of human umbilical cord mesenchymal stem cells (hUC-MSCs) in NOD. Cg-PrkdcscidIL2rgtm1Sug/JicCrl (NOG) mice.MethodsMice received subcutaneous hUC-MSC injections at doses of 2.5 × 107 and 2.0 × 108 cells/kg on days 1, 8, 12, 16, and 20, followed by withdrawal and observation for 6 weeks. Toxicity was assessed through clinical observation, behavioral analysis, pathology, organ weight measurements, and histopathology. hUC-MSC distribution was determined via validated quantitative (q)PCR and colonization was assessed using immunohistochemistry.ResultsNo abnormal effects on clinical responses, body weight, or food intake were observed following five repeated hUC-MSCs administrations, except for masses at the administration site in the high-dose group. Mouse activity levels increased in both dose groups 6 h post-final injection. Foamy cells were observed under the pleural membrane in high-dose mice. hUC-MSCs primarily colonized and were distributed within skin tissues 24 h after the last administration.ConclusionThe no-observed-adverse-effect level for subcutaneous hUC-MSC administration in NOG mice over 3 weeks was 2.5 × 107 cells/kg. Our results will help in advancing the clinical use of hUC-MSCs, particularly for treating conditions such as atopic dermatitis.